A Study on Factors Contributing Growth of Bancassurance - Diksha Sadana; Dr. Kamalpreet Kaur (HM Journals, 2023)
Banking and insurance industry is one of the determinants of the growth of financial sector of an economy as it contributes for the major part of the wealth of the nation. In the era of rapid changes and advancement where nothing is static let it be business products, competitors, needs and demands of various stakeholders, market capturing strategies etc. which drives the introduction of new distribution channels for banking and insurance industry as well and hence the concept of bancassurance emerged. Banking and insurance sectors not only strengthens economy economically but also enlarges the infrastructure base and giving risk taking abilities for new innovative ventures. Gone were the times where insurance services were considered as a privileged one and were meant only for the small part of financially dominant sector. Today the scenario has taken a complete U-turn where insurance sector is trying to reach to every person in almost every corner of the country and open new doors of opportunities for the banks which were earlier restricted only to accepting and advancing loans and so allowed the introduction of banks in the insurance business. With the help of secondary research this paper analyze the rationale behind bancassurance and also highlights effective operating model, attractive product, effective training, convincing motivators and well defined strategy as factors behind the success of bancassurance in India